GEOMECHANICAL ASPECTS OF PROBLEM OF OPENCAST EXPLOITATION OF DEPOSITS - Yakovlev V.L.; Sashurin A.D.; Zubkov A.V.; Yakovlev A.V. (My University, 2001)
Methodology of determining the slope of pit edge has been considered. New approaches to controlling the stability of pit edge have been discussed. Initial tectonic stresses and secondary stresses in rock mass have been taken into account. Mathematical models of phenomena arising during opencast exploitation of useful mineral deposits have been developed. Instrumental investigations of deformations of the pit edges and the adjoining territories have been performed. Satellite geodesy has been applied during the investigations. Behavior of rocks during opencast exploitation of deposits has been considered. Problems of safety have been discussed.